Az egészségügyi rendszer földrajzáról - Orosz, Éva (Tér és Társadalom, 1988)
What is the relationship between the geographical pattern of health care and the spatial variations in the state of health or the demographic features of the population? What processes produce spatio-social inequalities in the use of medical services? How can frequently contradicting requirements like efficency and equal access be conciliated in the process of shaping the spatiofunctional structute of health care? Such and similar questions are raised by a new discipline developing within societal geography or more closely, within medical geography – the geography of health care – from the beginning of the 1970s. The first part of the present paper gives an outline of the history of this new discipline and reviews the major branches of traditional medical geography: ailment-ecology; geographical epidemiology; spatial diffusion of maladies; studies on human nutrition. Recognizing health and ail ment as states of equlibrium and disequilibrium between man and his physical, biological and socio-cultural environments is not only a premise in ailment-ecology ibut also an important starting point in understanding the role, the activity and the socio-economic rel ationships of health care systems. The paper discusses the literature of health care geography in four major clusters of topics: the study of spatio-functional structure of health care; the spatial distribution of health care resources (physicians, hospital beds, finances); the access to and the use of medical services; the spatial aspects of planning in health care. The second part of the paper focusses on two major topics of the geography of health care: (1) the impact of distance decay function on the use of medical services; (2) the basic contradiction in the spatio-functional system of health care, i.e. the contradiction of concentration and access. The author underlines that the geography of health care is almost unknown in Hungary and the attitude of health care policy and planning towards spatial problems has stayed in the old rut beaten during the 1950s and 1960s.